2010
DOI: 10.5194/os-6-621-2010
|View full text |Cite
|
Sign up to set email alerts
|

Seismic imaging of a thermohaline staircase in the western tropical North Atlantic

Abstract: Abstract. Multichannel seismic data acquired in the Lesser Antilles in the western tropical North Atlantic indicate that the seismic reflection method has imaged an oceanic thermohaline staircase. Synthetic acoustic modeling using measured density and sound speed profiles corroborates inferences from the seismic data. In a small portion of the seismic image, laterally coherent, uniform layers are present at depths ranging from 550-700 m and have a separation of ∼ 20 m, with thicknesses increasing with depth. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 36 publications
2
46
0
Order By: Relevance
“…The local turbulent dissipation rate can be estimated by combining observations of the internal wave field (finescale measurements) with theoretical models of energy transfer. Finescale parameterizations have been widely used to estimate mixing in the past decade (e.g., Mauritzen et al 2002;Naveira Garabato et al 2004b;Sloyan 2005;Kunze et al 2006;Alford et al 2007;Park et al 2008;Fer et al 2010;Wu et al 2011;Whalen et al 2012;MacKinnon et al 2013). The use of finescale parameterization is high since the observations needed (vertical density and/or velocity measurements) to derive the dissipation rate with these methods are more easily acquired than direct observations of dissipation using microstructure profilers.…”
Section: Observationsmentioning
confidence: 99%
“…The local turbulent dissipation rate can be estimated by combining observations of the internal wave field (finescale measurements) with theoretical models of energy transfer. Finescale parameterizations have been widely used to estimate mixing in the past decade (e.g., Mauritzen et al 2002;Naveira Garabato et al 2004b;Sloyan 2005;Kunze et al 2006;Alford et al 2007;Park et al 2008;Fer et al 2010;Wu et al 2011;Whalen et al 2012;MacKinnon et al 2013). The use of finescale parameterization is high since the observations needed (vertical density and/or velocity measurements) to derive the dissipation rate with these methods are more easily acquired than direct observations of dissipation using microstructure profilers.…”
Section: Observationsmentioning
confidence: 99%
“…A recently developed method ''seismic oceanography'' based on the conventional seismic reflection profiling allows us to relate water column acoustic reflections to oceanic finescale structures [e.g., Holbrook et al, 2003;Ruddick et al, 2009]. It has the capability of showing the mesoscale to finescale features simultaneously with a typical vertical and horizontal resolution of 10 m. Numerous oceanographic features can be outlined successfully, such as subsurface eddies [Biescas et al, 2008;Buffett et al, 2009;Menesguen et al, 2012;Papenberg et al, 2010], currents [Tang et al, 2013;Tang and Zheng, 2011;Vsemirnova et al, 2012], internal waves [Holbrook and Fer, 2005;Krahmann et al, 2008], and thermohaline staircases [Biescas et al, 2010;Fer et al, 2010].…”
Section: Citationmentioning
confidence: 99%
“…The physical basis for seismic oceanography has been well established by several studies that combined seismic surveys with simultaneous in situ measurements of temperature, salinity, and density (Nakamura et al 2006;Nandi et al 2004;Sallar es et al 2009): weak, but clear, reflections from within the water column come from vertical changes in (primarily) sound speed and (secondarily) density. Over the past few years, numerous studies have demonstrated the ability of seismic imaging to detect and map major features in the ocean, including fronts (Holbrook et al 2003;Mirshak et al 2010;Sheen et al 2009), internal waves (Holbrook and Fer 2005;Krahmann et al 2008), eddies and warm-core rings (Biescas et al 2008;Ruddick et al 2009;Yamashita et al 2011), thermohaline staircases (Biescas et al 2010;Fer et al 2010), lee waves (Eakin et al 2011), and internal tide beams ). SO has several unique capabilities, including the ability to image fine structure over large sections of the ocean and to full ocean depth, provided that sufficient fine structure is present to produce reflections.…”
Section: Introductionmentioning
confidence: 99%